Rancang Bangun Aplikasi E-Museum Batik Sebagai Media Pembelajaran - Susanto, Wahyu Eko (Indonesian Journal on Software Engineering (IJSE), 2018)
Abstract - In addition to being a wealth of culture, national identity and become Indonesia. Batik also has a strategic role in the economic sphere. However, in its development of batik started having problems starting tergeser by printing of batik (batik Patterned Cloth) because the price is much cheaper. In addition to the lack of access to information to the young generation resulted in a decreased sense of passion and interest in the batik became one of the problems that resulted in the depletion of Human Resources regeneration craftsmen batik. middle of the slack of the E-museum visits the Museum into a solution of existing problems to open access to information, to introduce and provide education about batik in the midst of declining interest in the visit against the Museum. E Museum was built using Waterfall software development methods and Web-based. He made architecture with E batik Museum can be one of the means of delivery of information, introduce and educate the young generation to know the expectations of the younger generation of batik with more plays an active role in the preservation of batik. Keywords: Application, E Museum, Batik, Learning Media